Specificity and integration of meaning in self-defining memories of breast cancer survivors: clinical reflections to promote a narrative identity integration - Martino, Maria Luisa; Sebri, Valeria; Singer, Jefferson; Madow, Katie; Giudice, Alice Viola; Mazzoni, Davide; Freda, Maria Francesca; Pravettoni, Gabriella (Frontiers in Psychology, 2024)
Potential traumatic events, such as breast cancer, can influence autobiographical memory (AM), interrupting the continuity of narrative identity. AM is based on a hierarchical search across different levels of specificity that are indexed from top to bottom when a memory is retrieved. In the breast cancer field, non-specific AMs are an observed clinical phenomenon. In particular, breast cancer survivors report issues related to Self-Defining Memories (SDMs), specific and significant AMs that evoke strong emotions and sensory details at the time of memory. SDMs are linked to life goals and facilitate adaptation to critical experiences, preserving the continuity of identity. This study explored the narrative identity integration process of breast cancer survivors, analyzing themes, specificity, and integrative meaning in SDMs. 10 women participated in an online group support program centered on the integration of AMs linked to the cancer journey. Participants were asked to assess their Body Image perceptions, filling an online survey three times, in which they had to report 3 SDMs each time. A Reflexive Thematic Analysis of the SDMs identified three main themes: the onset of breast cancer; the labelling of negative emotions, and changes in the body. Results indicated inhibited retrieval of specific episodes, fostering a progressive failure in memory characterization and the concurrent meaning-making process. Participants struggled with connecting the memories to insights regarding their self and life, as well as relating the memories to external conditions and other individuals. Further studies might examine the impact of these difficulties on the psychological adjustment of BC long-term survivors. They could also explore cognitive reconstruction by reframing the memories and re-evaluating their traumatic meanings.